A prospective, randomised, controlled clinical study on the assessment of tolerability and of clinical efficacy of Merional (hMG-IBSA) administered subcutaneously versus Merional administered intramuscularly in women undergoing multifollicular ovarian stimulation in an ART programme (IVF) - Massobrio Marco; Strina Ida; Fedele Luigi; Ranieri Antonio; Anserini Paola; Revelli Alberto; Alviggi Carlo; Ragni Nicola; De Placido Giuseppe (BMC, 2007)
Abstract Background Multifollicular ovarian stimulation (MOS) is widely used in IVF and the compliance to treatment is deeply influenced by the tolerability of the medication(s) used and by the ease of self-administration. This prospective, controlled, randomised, parallel group open label, multicenter, phase III, equivalence study has been aimed to compare the clinical effectiveness (in terms of oocytes obtained) and tolerability of subcutaneous (s.c.) self-administered versus classical intramuscular (i.m.) injections of Merional, a new highly-purified hMG preparation. Methods A total of 168 normogonadotropic women undergoing IVF were enrolled. Among them, 160 achieved pituitary suppression with a GnRH-agonist long protocol and were randomised to MOS treatment with Merional s.c. or i.m. They started MOS with a standard hMG dose between 150-300 IU, depending upon patient's age, and underwent a standard IVF procedure. Results No statistically significant difference in the mean number of collected oocytes (primary endpoint) was observed between the two study subgroups (7.46, SD 4.24 vs. 7.86, SD 4.28 in the s.c. and i.m. subgroups, respectively). As concerns the secondary outcomes, both the pregnancy and the clinical pregnancy rates were comparable between subgroups. The incidence of adverse events was similar in the two groups (2.4% vs. 3.7%, respectively). Pain at injection site was reported only the i.m. group (13.9% of patients). Conclusion Merional may be used by s.c. injections in IVF with an effectiveness in terms of retrieved oocytes that is equivalent to the one obtained with i.m administration and with a better local tolerability. With the limitations due to the sample size af this study, s.c. and i.m. administration routes seem to have the same overall safety.